234Th as a tracer of vertical transport of polycyclic aromatic hydrocarbons in the northern Gulf of Mexico. Issue 1 (15th June 2016) - Adhikari, Puspa L.; Maiti, Kanchan; Bosu, Somiddho; Jones, Patrick R.
Abstract: Particle-mediated vertical flux of polycyclic aromatic hydrocarbons (PAHs) plays an important role in their removal from upper oceans and sets a limit on the amount delivered to the deep-sea sediments. In this study, we applied a one-dimensional steady-state 234 Th scavenging model to estimate vertical flux of PAHs in the northern Gulf of Mexico and compared them with sediment trap based flux estimates. The 234 Th-based ∑ PAH43 fluxes were 6.7 ± 1.0 μg m − 2  d − 1 and 3.7 ± 0.6 μg m − 2  d − 1 while sediment trap-based fluxes were 4.0 ± 0.6 μg m − 2  d − 1 and 4.5 ± 0.7 μg m − 2  d − 1 at 150 m and 250 m, respectively. Alkylated homologues contributed to 80% of the total PAH fluxes which is in contrary to other regions where combustion derived parent PAHs dominate the fluxes. The results indicate that the 238 U– 234 Th disequilibria can be an effective tracer of particulate PAH fluxes in upper mesopelagic zones and can provide flux estimates with high spatial coverage needed to quantify their long term fate and transport in the marine systems. Graphical abstract: Highlights: 234 Th-derived and sediment trap-based PAH fluxes at 150 and 250 m were found to be similar in the NGOM water column. 238 U − 234 Th disequilibria can be an effective tracer of particulate PAH fluxes in the upper mesopelagic zones. This technique can provide higher resolution PAH fluxes to quantify their long term fate & transport in the marine systems. Petrogenic PAHs contributed major fraction of total particulate PAH fluxes, making this region unique in the global oceans.